1981
DOI: 10.1037/0735-7028.12.3.400
|View full text |Cite
|
Sign up to set email alerts
|

Forensic training at internships: Update and criticism of current unspecified training models.

Abstract: In recent years, training opportunities in legal/forensic psychology have increased both at the graduate school and internship levels. Current data suggest that, at least at the internship level, the growth in this training is haphazard, uncoordinated, and unplanned and may have serious detrimental consequences for core training in psychology. Analysis of these trends is undertaken, and suggestions for an alternative legal/forensic training model are offered.In the 1970s, an increased interest in the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Kaslow and Abrams (1976) described details of a particular forensic program at Hahnemann Medical College and argued for the need to train psychologists in forensic work, which they described as turbulent, obviously a precursor of things to come. Later, Lawlor, Siskind, and Brooks (1981) (Durand, Blanchard, & Mindell, 1988;Piatrowski, 1984) concluded that, though many intern directors value projective techniques and expect interns to know these instruments, the academic community was less supportive regarding their value. One study noted a decline in the role for projective techniques.…”
Section: What Interns Should Be and Are Taughtmentioning
confidence: 99%
“…Kaslow and Abrams (1976) described details of a particular forensic program at Hahnemann Medical College and argued for the need to train psychologists in forensic work, which they described as turbulent, obviously a precursor of things to come. Later, Lawlor, Siskind, and Brooks (1981) (Durand, Blanchard, & Mindell, 1988;Piatrowski, 1984) concluded that, though many intern directors value projective techniques and expect interns to know these instruments, the academic community was less supportive regarding their value. One study noted a decline in the role for projective techniques.…”
Section: What Interns Should Be and Are Taughtmentioning
confidence: 99%
“…Kaslow and Abrams (1976) de-scribed details of a particular forensic program at Hahnemann Medical College and argued for the need to train psychologists in forensic work, which they described as turbulent, obviously a precursor of things to come. Later, Lawlor, Siskind, and Brooks (1981) determined that forensic training was more prevalent but characterized it as haphazard, uncoordinated, and unplanned.…”
Section: What Interns Should Be and Are Taughtmentioning
confidence: 99%
“…The purpose of this article is not to provide an exhaustive list and descriptions of all forensic training and credentialing opportunities. Readers seeking this information are directed elsewhere (Heilbrun & Annis, 1988;Lawlor, Siskind, & Brooks, 1981;Levine, Wilson, & Sales, 1980;Ogloff, 1990;Roesch et al, 1986).…”
Section: R K Otto E T Dmentioning
confidence: 99%